Radio-optical line for SCADA systems with relay. Issue 5 (May 2020) - Krasnov, R P; Ostankov, A V; Malyshev, I I; Maximov, D A; Kondusov, V A
Abstract: Hybrid optical-radio communication systems provide high-speed access within the "last mile" and can act as highly reliable broadband channels of SCADA software and hardware systems. They use optical channels as the main communication lines, and radio channels as backup, since the transmission quality of atmospheric optical channels is largely determined by weather conditions. To reduce the effect of atmospheric turbulence, it is proposed to use the option of spatial diversity with line-of-sight channels and containing a repeater. When the signal-to-noise ratio decreases in the optical channel below the selected threshold, switching to the radio link is to be performed. The paper provides the results of modeling the operation of a hybrid radio-optical line in SCADA systems, in which a new switching system for optical and radio-frequency channels using a repeater is proposed. The dependences of the outage probability of the optical channel and the system as a whole are obtained.